The CD40–CD40L Dyad in Experimental Autoimmune Encephalomyelitis and Multiple Sclerosis - Aarts, Suzanne A. B. M.; Seijkens, Tom T. P.; van Dorst, Koos J. F.; Dijkstra, Christine D.; Kooij, Gijs; Lutgens, Esther (Frontiers in Immunology, 2017)
The CD40–CD40L dyad is an immune checkpoint regulator that promotes both innate and adaptive immune responses and has therefore an essential role in the development of inflammatory diseases, including multiple sclerosis (MS). In MS, CD40 and CD40L are expressed on immune cells present in blood and lymphoid organs, affected resident central nervous system (CNS) cells, and inflammatory cells that have infiltrated the CNS. CD40–CD40L interactions fuel the inflammatory response underlying MS, and both genetic deficiency and antibody-mediated inhibition of the CD40–CD40L dyad reduce disease severity in experimental autoimmune encephalomyelitis (EAE). Both proteins are therefore attractive therapeutic candidates to modulate aberrant inflammatory responses in MS. Here, we discuss the genetic, experimental and clinical studies on the role of CD40 and CD40L interactions in EAE and MS and we explore novel approaches to therapeutically target this dyad to combat neuroinflammatory diseases.